Actin filaments in sensory hairs of inner ear receptor cells (The Rockefeller University Press, 1977)
Receptor cells in the ear are excited through the bending of sensory hairs which project in a bundle from their surface. The individual stereocilia of a bundle contain filaments about 5 nm in diameter. The identity of these filaments has been investigated in the crista ampullaris of the frog and guinea pig by a technique of decoration with subfragment-1 of myosin (S-1). After demembranation with Triton X-100 and incubation with S-1, "arrowhead" formation was observed along the filaments of the stereocilia and their rootlets and also along filaments in the cuticular plate inside the receptor cell. The distance between attached S-1 was 35 nm and arrowheads pointed in towards the cell soma. It is concluded that the filaments of stereocilia are composed of actin.